Hepatocytes cocultured with Sertoli cells in bioreactor favors Sertoli barrier tightness in rat. Issue 3 (21st July 2016) - Zeller, P.; Legendre, A.; Jacques, S.; Fleury, M. J.; Gilard, F.; Tcherkez, G.; Leclerc, E.
Abstract : The lack of a reliable in vitro system to assess reprotoxicity is an emerging problem in the context of European law for Registration, Evaluation, Authorization and Restriction of Chemicals (REACH, 2007), as it requires a reduction in animal utilization for testing. Furthermore, in vitro reprotoxicological tests would be more relevant and greatly improved by integrating both hepatic metabolism and the blood–testis barrier. Here, we took advantage of an integrated insert in a dynamic microfluidic platform (IIDMP) to co‐cultivate hepatocytes in biochip and Sertoli cells in the bicameral chamber. This microfluidic tool has been previously demonstrated to be helpful in cell function and/or quality improvement. We demonstrate that permeability of the Sertoli barrier is reduced by dynamic coculture in our system. Exometabolomics analysis reveals that interactions between hepatocytes and Sertoli cells may have been mediated by the polyamines increase and/or mid‐chain fatty acid decrease in the circulating medium. These metabolic changes may be involved in permeability reduction by contributing to modifying junction protein quantity and localization. The present study gives an example of IIDMP as an in vitro partitioning/transport model for cell culture and toxicological testing. Further, based on both our previous results using an intestinal–hepatic cell coculture and the present study, IIDMP seems to be well‐suited for (i) assessing the dose–response effect of chemicals within the rodent or human male reproductive tract, and (ii) improving the quality of reprotoxicological assays by including hepatic metabolism. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The lack of a reliable in vitro system to assess reprotoxicity is an emerging problem. Here, we integrated hepatic metabolism and the blood–testis barrier using a culture insert within a dynamic microfluidic platform system (IIDMP). We demonstrate that permeability of the barrier is reduced by dynamic coculture. IIDMP seems to be well suited for (i) assessing the dose–response effect of chemicals within the rodent or human male reproductive tract, and (ii) improving the quality of reprotoxicological assays by including hepatic metabolism.